MEMPERSIAPKAN PENATUA SEBAGAI PENDUKUNG PELAYANAN DI GEREJA KRISTEN SETIA INDONESIA JEMAAT ISA ALMASIH TAMAN MINI - Jonidius Illu; Mozes Lawalata; Yeremia Hia; Sandra Rosiana Tapilaha (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
Some of the main issues that will be discussed in this paper include: 1) there is an assumption from the congregation that the ministry is only the pastor's job because he has attended special lessons in theological colleges; 2) the role of elders is not optimal because the pastor of the church does not prepare them through coaching; 3) elders do not carry out their duties to the fullest because they do not understand. The purpose of the research is to provide an understanding that the ministry's task is not only carried out by the pastor of the church, that's why it is necessary to prepare coaching for prospective elders to provide support for the ministry. Involving elders needs to start with coaching to understand God's Word and their ministry role. The method used is lectures and training with the hope that it can provide an understanding to the prospective assemblies that service is also their responsibility.